Subsurface heat channel drove sea surface warming in the high-latitude North Atlantic during the mid-pleistocene transition - Amorim Catunda, Maria Carolina; Bahr, André; Kaboth-Bahr, Stefanie; Zhang, Xu; Foukal, Nicholas P.; Friedrich, Oliver (Geophysical research letters, 2021)
The Mid-Pleistocene Transition (MPT, 1,200-600 ka) marks the rapid expansion of Northern Hemisphere (NH) continental ice sheets and stronger precession pacing of glacial/interglacial cyclicity. Here, we investigate the relationship between thermocline depth in the central North Atlantic, subsurface northward heat transport and the initiation of the 100-kyr cyclicity during the MPT. To reconstruct deep-thermocline temperatures, we generated a Mg/Ca-based temperature record of deep-dwelling (∼800 m) planktonic foraminifera from mid-latitude North Atlantic at Site U1313. This record shows phases of pronounced heat accumulation at subsurface levels during the mid-MPT glacial driven by increased outflow of the Mediterranean Sea. Concurrent warming of the subtropical thermocline and subpolar surface waters indicates enhanced (subsurface) inter-gyre transport of warm water to the subpolar North Atlantic, which provided moisture for ice-sheet growth. Precession-modulated variability in the northward transport of subtropical waters imprinted this orbital cyclicity into NH ice-sheets after Marine Isotope Stage 24.
Gesehen am 12.08.2021